“Actividades grafoplásticas para fortalecer el esquema corporal en los niños de Educación Inicial” - Chilig Caiza, Diana Magdalena (2024)
In this research project, difficulties were identified in the area of body schema and the lack of application of graphoplastic techniques considering that it is a fundamental part of the educational process in early childhood. The objective of this research was to design graphoplastic activities to strengthen the body schema in early childhood education children. On the other hand, constructivism is taken as a pedagogical approach, which affirms that education should be dynamic. The methodological design of the research was defined in the qualitative approach, oriented towards a descriptive bibliographic research with the use of the inductive method that allowed the elaboration of the proposal. The techniques used in the research were the interview, which was applied to the teachers, as well as, an observation form for the children, obtaining direct and valuable information on the current situation of the development of the body schema. As a result, 10 activities are described in the research proposal, this allowed for reaching the following conclusion for the construction of graphoplastic activities that favor the strengthening of the body scheme, which is why, it is necessary to know the benefits that this generates in the first childhood.